Annual Bulletin of Statistics on Cocoa, Coffee and Tea - Nigerian Cocoa Board (Ibadan, 1982)
This is the third edition of the Annual Bulletin of Statistics on Cocoa, Coffee and Tea. It contains weekly production figures in respect of each of the producing states from that year.
usc 17/08/2021
Ref
Keywords: Cocoa production; Nigeria